Risk factors for in-hospital mortality after total arch procedure in patients with acute type A aortic dissection - An, Zhao; Zhong, Keng; Sun, Yangyong; Han, Lin; Xu, Zhiyun; Li, Bailing (Frontiers in Cardiovascular Medicine, 2023)
Object: Knowledge about the risk factors of in-hospital mortality for acute type A aortic dissection (ATAAD) patients who received total arch procedure is limited. This study aims to investigate preoperative and intraoperative risk factors of in-hospital mortality of these patients. Methods: From May 2014 to June 2018, 372 ATAAD patients received total arch procedure in our institution. These patients were divided into survival and death groups and patients` in-hospital data were retrospectively collected. Receiver operating characteristic (ROC) curve analysis was adopted to determine the optimal cut-off value of continuous variables. Univariate and multivariable logistic regression analysis was used to detect independent risk factors for in-hospital mortality. Results: 321 patients were included in survival group and 51 patients were in death group. Preoperative details showed patients in death group were older (55.4 ± 11.7 vs 49.3 ± 12.6, P = 0.001), had more renal dysfunction (29.4% vs 10.9%, P = 0.001) and coronary ostia dissection (29.4% vs 12.2%, P = 0.001) and with decreased left ventricular ejection fraction (LVEF) (57.5 ± 7.9% vs 59.8 ± 7.3%, P = 0.032). Intraoperative results showed more patients in death group experienced concomitant coronary artery bypass grafting (CABG) (35.3% vs 15.3%, P = 0.001) with increased cardiopulmonary bypass (CPB) time (165.7 ± 39.0 vs 149.4 ± 35.8 min, P = 0.003), Cross-clamp time (98.4 ± 24.5 vs 90.2 ± 26.9 min, P = 0.044) and red blood cells (RBCs) transfusion (913.7 ± 629.0 vs 709.7 ± 686.6 ml, P = 0.047). Logistic regression analysis showed age > 55 years, renal dysfunction, CPB time > 144 minutes and RBCs transfusion > 1300 ml were independent risk factors for in-hospital mortality in patients with ATAAD. Conclusion: In the present study, we identified older age, preoperative renal dysfunction, long CPB time and intraoperative massive transfusion were risk factors for in-hospital mortality in ATAAD patients with total arch procedure.